Antihypertensive Effect of a Novel Angiotensin II Receptor Blocker Fluorophenyl Benzimidazole: Contribution of cGMP, Voltage-dependent Calcium Channels, and BKCa Channels to Vasorelaxant Mechanisms - Iqbal, Hina; Verma, Amit Kumar; Yadav, Pankaj; Alam, Sarfaraz; Shafiq, Mohammad; Mishra, Divya; Khan, Feroz; Hanif, Kashif; Negi, Arvind Singh; Chanda, Debabrata (Frontiers in Pharmacology, 2021)
Background: The present study reports novel angiotensin II receptor blocker fluorophenyl benzimidazole (FPD) as an antihypertensive agent in the SHR model of hypertension. We have investigated the role of cGMP, voltage-dependent L-type calcium channels, and BKca channel in the vasorelaxant mechanisms of FPD in the rat superior mesenteric artery. Methods: The antihypertensive effect of FPD was examined using invasive technique of blood pressure measurement in SHR animals. Using a myograph, tension measurement was done in the superior mesenteric artery to elucidate the mechanisms of vasorelaxation involving AT1 receptors, NO/cGMP pathway, L-type calcium channels, and BKca channels. Ion flux (Ca2+, K+) studies were conducted in aortic smooth muscle cells. Putative targets proteins were determined by in-silico docking studies. Safety evaluation of FPD was carried out in Swiss albino mice. Results: FPD significantly decreased blood pressure in SHR. It relaxed superior mesenteric arteries in concentration dependent manner and significantly inhibited angiotensin II-induced contraction. The relaxation response was also mediated by an increase in tissue cGMP levels, inhibition of L-type calcium channels, and opening of BKca channels. FPD further enhanced efflux of K+ and inhibited BAY K8644-stimulated Ca2+ influx in aortic smooth muscle cells and docked well in in-silico study with the targets. It was well tolerated in the toxicity study. Conclusion: The present study reports antihypertensive activity of novel AT-1 receptor blocker FPD at 50 and 100 mg kg-1 with cGMP, L-type calcium channels, and BKca channels as putative targets and was found safe in oral toxicity.